The 50 most cited studies on posterior tibial slope in joint preserving knee surgery - Romed P. Vieider; Daniel P. Berthold; Armin Runer; Philipp W. Winkler; Phillip Schulz; Marco‐Christopher Rupp; Sebastian Siebenlist; Lukas N. Muench (Journal of Experimental Orthopaedics)
Abstract Purpose To determine the 50 most cited studies on posterior tibial slope (PTS) in joint preserving knee surgery and assess their level of evidence, objective study quality scores as well as to examine whether the study quality correlated with the citation count and citation density in the top 50 list. Methods A literature search on Web of Science was performed to determine the 50 most cited studies on the topic of PTS in joint preserving knee surgery between 1990 and 2022. The studies were evaluated for their bibliographic parameters, level of evidence rating (LOE), citation counts, the Modified Coleman Methodological Score (MCMS), the Methodological Index for Non‐Randomized Studies (MINORS), and the Radiologic Methodology and Quality Scale (MQCSRE). Results Of the top 50 list, 16 studies were published in the American Journal of Sports Medicine. A total of 23 studies were produced in the United States (46%). Of 10 different study types, case control studies (n = 16, 32%) and cadaveric studies (n = 10, 20%) were most common. 15 studies (30%) were purely radiological studies. 6 studies were level II (12%), 23 level III (46%), 15 level IV (30%), and 6 level V studies (12%), respectively. The number of citations ranged from 42 to 447 (mean 105.6 ± 79.2 citations) and showed a mean citation density of 10.3 ± 5.2, composed of the decades 1994 – 2000 (8.3 ± 4.1), 2001 – 2010 (11.1 ± 5.9), 2011 – 2019 (10.1 ± 5.1). Mean quality scores were 55.9 ± 13.0 for MCMS (n = 18), 14.5 ± 3.2 for MINORS (n = 18) and 18.1 ± 3.7 for MQCSRE (n = 20), respectively. High citation counts did not correlate with higher study quality scores (p > 0.05). Radiological studies were not significantly cited more often than non‐radiological studies (mean 116.9 ± 88.3 vs. 100.8 ± 75.8 citations; p > 0.05). Conclusion In joint preserving knee surgery, the 50 most cited studies on PTS did not represent a ranking of the highest methodological quality scores. Citation counts and citation density over the past three decades did not significantly differ, even though the number of articles in the presented list multiplied over the same period. This list can serve as a reference tool for orthopedic surgeons aiming to review PTS literature.